But Does It Work?: The Influence of Presumed Goal Attainment Effectiveness on Willingness to Use Legalistic and Restorative Responses to Offensive Behavior. Issue 2 (14th March 2016) - Paul, Gregory D.
Abstract : Although victim-offender conferences (VOCs) ostensibly enable victims to pursue justice goals not achieved through conventional trials, not all victims wish to participate in them. The purpose of this study was to examine how victims' presumptions regarding the effectiveness of VOCs and trials in accomplishing justice goals influence their willingness to participate in a VOC and their preference for a case to be managed solely by the courts. Study results indicated that participants believed VOCs and trials to be effective at accomplishing different goals and that such influenced how they wanted cases to be managed. This influence was moderated by desires for particular justice goals. These findings have implications for restorative justice researchers and practitioners interested in victims' motivations to participate in a VOC.